A case of disseminated intravascular coagulation following tumour lysis syndrome due to small cell carcinoma of the lung. Issue 3 (6th February 2023) - Takahashi, Saeko; Takehara, Tomohiro; Tani, Tetsuo; Ishioka, Kota; Madoiwa, Seiji
Abstract: A 64‐year‐old man was diagnosed with small cell lung cancer (SCLC) with multiple bone and liver metastases and bone marrow metastases. Spontaneous tumour lysis syndrome (TLS) was observed before starting chemotherapy with carboplatin, etoposide, and atezolizumab. The tumour further collapsed, and the patient developed disseminated intravascular coagulation (DIC) on day 4 of chemotherapy. The patient was successfully treated with intravenous hydration and rasburicase for TLS and subcutaneous unfractionated heparin for DIC. A large amount of tissue factor may be released in TLS, which could induce DIC. However, to the best of our knowledge, this is the first report of DIC following TLS in a case of SCLC. DIC following TLS in SCLC is a rare but life‐threatening oncologic complication. Therefore, clinicians should be aware of this possibility when treating patients with advanced SCLC. Abstract : Disseminated intravascular coagulation (DIC) following tumour lysis syndrome (TLS) is a rare but serious life‐threatening complication that clinicians need to be aware of when treating patients with advanced small cell lung cancer (SCLC). To the best of our knowledge, this is the first report of DIC following TLS in a case of SCLC.